Avaliação da altura do leito de sinterização de finos de minério de ferro em um reator vertical de leito fixo para a produção de sínter - DANIEL, Brenda Thayssa Figueira (2018)
The objective of the present work is to perform the sintering process of iron ore fines, charcoal mill and additions, in three heights, of a Fixed Bed Reactor and to analyze the process parameters as well as the performance of the equipment and the quality of the sinter produced. Said process has the purpose, the production of a sinter for the reduction process in blast furnaces. The mechanical strength of the sinter will depend on the amount and composition of the sintering mixture. In this way, the products obtained were characterized by analyzes in DRX, MEV, EDS and FRX, submitted to tumbling tests. At the end, it can be stated that the best sinter bed height achieved, among the three studies carried out here, Sínter 2, with a height of 45 cm, obtained satisfactory results in real sintering temperatures and consequently generating sinters with good quality for pilot plant production.